Cholesterol homeostasis and pathway enrichment in post-revascularization recovery - Syed Abdullah Basit; Nehad M. Alajez; Tanvir Alam (BioMedical Engineering OnLine)
Abstract Background Heart revascularization is a critical intervention for restoring myocardial perfusion in patients with ischemic cardiovascular disease. While the procedure alleviates ischemia, it also triggers systemic metabolic and transcriptional changes, particularly in lipid metabolism. Methods In this pilot study, we utilized RNA-seq data from 4 revascularized patients and 5 control participants from the Qatar Biobank (QBB) to investigate the effects of revascularization on cholesterol biosynthesis and metabolic pathways. Differential gene expression analysis was performed to identify key regulatory genes, followed by pathway enrichment and Gene Ontology analyses. Results Thirteen differentially expressed genes, including ABCG1, EBP, and LPCAT3, were identified as potentially involved in cholesterol regulation, lipid remodeling, and sterol metabolism. Notably, ABCG1, EBP, and LPCAT3 showed significant downregulation. Correlation analysis revealed strong associations between gene expression and clinical parameters, with ABCG1 expression negatively correlating with triglyceride levels (r = − 0.89, p = 0.001). Conclusion This exploratory study provides preliminary evidence that heart revascularization may affect cholesterol-related metabolic pathways. While the small sample size (n = 4 revascularized patients) limits generalizability, these findings generate important hypotheses regarding post-revascularization metabolic adaptation and establish a foundation for larger validation studies. Future research with expanded cohorts is essential to confirm these preliminary observations and their therapeutic implications.